2011
DOI: 10.1155/2011/360292
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health-Related Quality of Life of Greek Adults: A Cross-Sectional Study

Abstract: Purpose. The aim of the present study was to investigate the impact of oral health status on the quality of life of adults in different regions of Greece, using the Oral Health Impact Profile-short form (OHIP-14). Methods. A random sample consisting of a total of 504 Greek adults between the ages of 35–44 years (mean 39.1 ± 3.5) was selected from different urban and rural areas, and face-to-face interviews were conducted using the validated Greek language OHIP-14. Associations of the total OHIP-14 score and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 13 publications
5
19
1
4
Order By: Relevance
“…The present findings for Greek seniors revealed a medium impact of oral health with a weighted OHIP-14 score of 2.1, higher than the findings for the adolescents (1.2) [20] and young adults (1.1) [21], confirming the previous reports of a relatively low effect for the Greek population as a whole. This finding is somewhat lower than what a similar study found for Norwegian elders [25], which reported an OHIP-14 score of 3.4, as well as to the levels of impact that were reported for South Australians, i.e., 4.8 [23].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The present findings for Greek seniors revealed a medium impact of oral health with a weighted OHIP-14 score of 2.1, higher than the findings for the adolescents (1.2) [20] and young adults (1.1) [21], confirming the previous reports of a relatively low effect for the Greek population as a whole. This finding is somewhat lower than what a similar study found for Norwegian elders [25], which reported an OHIP-14 score of 3.4, as well as to the levels of impact that were reported for South Australians, i.e., 4.8 [23].…”
Section: Discussionsupporting
confidence: 80%
“…For the specific age group of elderly adults, it has been shown in a study by Hebling and Pereira [19] that the OHIP-14 instrument can be considered an instrument of choice, along with 6 other instruments that they set apart out of a larger pool of similar questionnaires. Indeed, the instrument was found here to have a very high internal consistency with a Cronbach α of 0.89, which reflects the results reported when used for the other age groups [20,21]. Moreover, this is the first study to examine a representative sample of this elderly section of the Greek population concerning oral health quality of life.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…3 QoL measures are of importance in order to look further than just the presence of health or disease and into the way that impacts on his daily performance. 4 The key to improve QoL is by repatriating oral function, mastication, preventing oral disease, repairing oral tissue, and tackling the patient's complaints. 1 Oral health-related quality of life (OHRQoL) is defined as a multidimensional construct that reflects (among other things) people's comfort when eating, sleeping, and engaging in social interaction; their self-esteem; and their satisfaction with respect to their oral health.…”
Section: Introductionmentioning
confidence: 99%